Penerapan Metode Hungarian Dalam Optimasi Biaya Marketing Pada Pt. Jovi Karunia Jaya - Nofranti Samosir (JURIKOM (Jurnal Riset Komputer), 2019)
Marketing is a person who works in marketing, able to serve, market, able to interact directly with consumers. In the business world more and more rivals are able to drop or create a bankrupt company, if it has a high expenditure while the income is small. Companies that go bankrupt because of the cost to employees are too large like in completing the work when doing product offer marketing letters. Each employee has an assignment fee for different jobs, because the nature or manner of each job is different. Every employee has different skill level, work experience, different educational background, so it requires different cost, so the cost to each employee must be minimized.